2014
DOI: 10.24059/olj.v18i4.512
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology to Facilitate Learning for Students in the Health Professions: Current Uses, Gaps and Future Directions

Abstract: Changes in the U.S. Healthcare System along with the need for institutions of higher education to prepare a work force ready to address the challenges of today and tomorrow have highlighted the need to incorporate technology in its broadest sense as part of the student learning experience. In health professional education, this becomes challenging as programs have traditionally relied on face-to-face instruction along with internship experiences which provide hands on patient care. In addition, learning activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Most of the literature addressing how educators are prepared for teaching in blended and online learning environments is from primary and secondary education settings (Luo, Hibbard, Franklin, & Moore, 2017;Shepherd, Bolliger, Dousay, & Persichitte, 2016). Research has shown that teaching in blended and online learning environments requires different pedagogical approaches (theories, methods, and activities) than teaching face-to-face (Dereshiwsky, 2013;Sadera, O'Neil, & Gould, 2014) and is often more challenging (Allen & Seaman, 2013;Costello et al, 2014;Swan et al, 2008). Challenges to teaching from a distance are often related to the absence of nonverbal methods of communication, such as facial expressions and voice inflections (Rovai & Jordan, 2004).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Most of the literature addressing how educators are prepared for teaching in blended and online learning environments is from primary and secondary education settings (Luo, Hibbard, Franklin, & Moore, 2017;Shepherd, Bolliger, Dousay, & Persichitte, 2016). Research has shown that teaching in blended and online learning environments requires different pedagogical approaches (theories, methods, and activities) than teaching face-to-face (Dereshiwsky, 2013;Sadera, O'Neil, & Gould, 2014) and is often more challenging (Allen & Seaman, 2013;Costello et al, 2014;Swan et al, 2008). Challenges to teaching from a distance are often related to the absence of nonverbal methods of communication, such as facial expressions and voice inflections (Rovai & Jordan, 2004).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Instructors across disciplines have integrated a variety of Web 2.0 tools to add interactivity to online courses and/or to supplement face-to-face lectures. [24][25][26][27][28][29] This study focused on a Web 2.0 tool called Voicethread, a cloud-based multimedia presentation tool. It allows instructors to create presentations using Dental Education Association (ADEA) Survey of Dental School Seniors.…”
Section: Online Learning and Web 20 Technologymentioning
confidence: 99%
“…Complex online virtual simulation (OVS) learning experiences increase student knowledge and exposure and engagement with the diagnostic reasoning process; yet, there is little evidence of the effectiveness of this technology for teaching and learning diagnostic reasoning (Costello et al, 2014;Tichon, 2012). The purpose of this scoping review was to examine the use of OVS in health care education, identify the technologies used, and evaluate the effectiveness of OVS in teaching diagnostic reasoning.…”
mentioning
confidence: 99%